Rancangan Undang-Undang Penghapusan Kekerasan Seksual (RUU PKS) dalam Perspektif Maslahah Mursalah - Tamam, Ahmad Badrut (Proceedings of Annual Conference for Muslim Scholars, 2019)
The pros and cons of the Bill on the Elimination of Sexual Violence (RUU PKS), one of which is caused by a conflict between two different perspectives in understanding it. The pro-camps tend to use a gender perspective, they base their support on the academic text of the RUU PKS which explicitly states that the formulation of this bill uses the perspective of women (feminist legal theory). The emphasis of this gender perspective is on the experience of victims, especially women. Meanwhile, the counter RUU PKS tends to use a religious perspective. They argue that the RUU PKS eliminates religious norms because it uses a gender perspective adopted from a secular West. For this group, the root of the problem of sexual violence that has occurred so far is not because of inequality in gender relations, but because of the malfunctioning of family institutions, so the solution should be to return to religious norms. If you catch a glimpse of the arguments of groups who reject, then it seems that the RUU PKS is against religion.